PENGARUH TATA KELOLA PERUSAHAAN TERHADAP MANAJEMEN LABA AKRUAL - Rachelya Viodolin Manurung; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2020)
The purpose of this research is to examine the effect of corporate governance (CG) on earnings management (EM) in Indonesia. The independent used in this research are board independence, board gender diversity, director’s share ownership, and audit quality while the dependent variabel used in this research is earnings management. This research uses multiple regression analysis method with secondary data obtained by purposive sampling method. The sample comprises of 161 companies listed in Indonesian Stock Exchange. The Research data is secondary data from financial statements and annual reports of non financial firm over the period 2018. The results of this research indicate that board independence, board gender diversity, director’s share ownership, and audit quality were negatively and significantly related to earnings management.